GLP-1 Receptor Activation Inhibits VLDL Production and Reverses Hepatic Steatosis by Decreasing Hepatic Lipogenesis in High-Fat-Fed APOE*3-Leiden Mice - Parlevliet, Edwin T.; Wang, Yanan; Geerling, Janine J.; Schröder-Van der Elst, Janny P.; Picha, Kristen; O'Neil, Karyn; Stojanovic-Susulic, Vedrana; Ort, Tatiana; Havekes, Louis M.; Romijn, Johannes A.; Pijl, Hanno; Rensen, Patrick C. N. (PLOS ONE, 2012)
Objective In addition to improve glucose intolerance, recent studies suggest that glucagon-like peptide-1 (GLP-1) receptor agonism also decreases triglyceride (TG) levels. The aim of this study was to evaluate the effect of GLP-1 receptor agonism on very-low-density lipoprotein (VLDL)-TG production and liver TG metabolism. Experimental Approach The GLP-1 peptide analogues CNTO3649 and exendin-4 were continuously administered subcutaneously to high fat diet-fed APOE*3-Leiden transgenic mice. After 4 weeks, hepatic VLDL production, lipid content, and expression profiles of selected genes involved in lipid metabolism were determined. Results CNTO3649 and exendin-4 reduced fasting plasma glucose (up to −30% and −28% respectively) and insulin (−43% and −65% respectively). In addition, these agents reduced VLDL-TG production (−36% and −54% respectively) and VLDL-apoB production (−36% and −43% respectively), indicating reduced production of VLDL particles rather than reduced lipidation of apoB. Moreover, they markedly decreased hepatic content of TG (−39% and −55% respectively), cholesterol (−30% and −55% respectively), and phospholipids (−23% and −36% respectively), accompanied by down-regulation of expression of genes involved in hepatic lipogenesis (Srebp-1c, Fasn, Dgat1) and apoB synthesis (Apob). Conclusion GLP-1 receptor agonism reduces VLDL production and hepatic steatosis in addition to an improvement of glycemic control. These data suggest that GLP-receptor agonists could reduce hepatic steatosis and ameliorate dyslipidemia in patients with type 2 diabetes mellitus.